The Effect of Inventory Control on the Work Productivity of Inventory Division Employees at PT Duta Sentosa Yasa (MR DIY) KBN Marunda - Kesumo, Sabil Wijoyo; Suprayitno, Degdo; Latunreng, Wahyuddin (Yayasan Sinergi Kawula Muda, 2024)
This study examines the effect of Inventory Control on Work Productivity of the Inventory Division at PT. Duta Sentosa Yasa (MR.DIY) KBN Marunda. The population in this study is only employees of the Inventory division. The number of samples used is 65 people who employees of the Inventory division. The sampling technique uses the saturated sample technique. Data analysis used validity test, reliability test, classical assumption test, normality test, linearity test, simple linear regression analysis, coefficient of determination test and t test. The analysis shows that Inventory Control has a positive influence on Work Productivity. The results showed that the validity test that r count is greater than the r table value of 0.244 with a significant level of 5% and n: 65. Thus, the conclusions of this study indicate that there is a significant influence between Inventory Control on Work Productivity of 59.9% while 40.1% is influenced by other variables.